Cultivar Identification of 55 Korean Peanut Varieties via Selection of Informative SNP Markers from Microarray Genotyping - Eunyoung Oh; Sungup Kim; Jung In Kim; Min-young Kim; Jeongeun Lee; Sang-woo Kim; Eunsoo Lee; Rizwana Syed Begum Nabi; Myoung Hee Lee; Kwang-soo Cho (Plant breeding and biotechnology, 2023)
Peanut variety identification is essential for protecting the intellectual property rights of researchers, ensuring quality management for producers, and safeguarding the interests of seed production stakeholders. In this research, we developed a molecular marker set for peanut variety identification using single nucleotide polymorphism (SNP) markers. We used genotyping data and selection procedures, including decision tree and optimal combination selection, to identify a minimal set of informative SNP sites. These SNPs were then converted into Kompetitive allele-specific PCR (KASP) markers. We selected a subset of 14 informative SNPs from a pool of 22 candidate markers, representing the minimum number of combinations required to distinguish cultivars. SNPs obtained from the microarrays were converted to KASP markers and then evaluated across 51 peanut varieties. The developed marker set, which consists of a minimal number of markers, is expected to be a rapid and cost-effective tool for peanut variety identification.